The use of poly(lactic-co-glycolic acid) and fibrin scaffolds for articular cartilage tissue engineering - Abdul Rahman, Rozlin; Sha'ban, Munirah; Mohamad Sukri, Norhamiza; Md Nazir, Noorhidayah; Ahmad Radzi, Muhammad Aa'zamuddin; Mohamad, Mohd Yusof; Abdul Rahman, Suzanah; Zulkifly, Ahmad Hafiz; Che Ahmad, Aminudin (2014)

(untitled)
Introduction: Damage and degeneration of articular joints is a major health concern. Left untreated, it may cause serious disability and loss of function. The field of cartilage tissue engineering which aims to restore, repair and regenerate injured articular cartilage has evoked numerous interest for improving cartilage functionality. Previously, the use of Poly(Lactic-coGlycolic Acid) or PLGA and fibrin scaffolds indicated some potentials for in vitro cartilaginous tissue formation. The cells used were adult progenitor or committed cells isolated from mature cartilage - the chondrocyte. For this study, the aim was to evaluate the formation of in vitro cartilaginous construct using bone marrow mesenchymal stem cells or BMSCs-seeded on PLGA with or without fibrin scaffold. Methods and materials: With the approval of Research Ethical Committee, aspirated rabbit’s BMSCs were processed and cultured in the commercially available chondrogenic media. The resulted mononuclear cells were expanded to obtain sufficient cell number for three dimensional (3-D) construct formation. Macroscopic evaluation, histological evaluation, cell proliferation assay and sulphated glycosaminoglycan (sGAG) analyses were performed at each time point of 1, 2 and 3 weeks of in vitro culture. Results: After 3 weeks, the BMSCs/PLGA/fibrin constructs showed a reduction in terms of size. The cells were noted to segregate mainly on the outer part of the construct instead of migrating towards the inner part of the construct. However the BMSCs/PLGA/fibrin construct exhibited higher cell viability, higher sGAG content and better extracellular matrix compound in concert with the positive GAG accumulation than the BMSCs/PLGA without fibrin construct. Conclusion: Although the histology results showed lack of cartilaginous histo-architecture, PLGA/fibrin seeded with BMSCs indicated a potential to develop as functional tissue engineered cartilage which could facilitate and improve the life quality of patients suffering from joint diseases. At the moment, gene expression studies are being carried out to evaluate the expression of specific cartilaginous markers in BMSCs-seeded on PLGA with or without fibrin.